Analyze the future form of AI spreading Chinese opera video - Yang Yuejia; Lee KuokTiung; Ng Wei Liang (Human Resource Management Academic Research Society, 2024)
AI Artificial Intelligence is increasingly being used in all aspects of life, and AI is also being used in traditional Chinese opera. This paper collects the current application of AI in current drama videos from the aspects of AI video repair, drama script generation, VR watching drama and so on. According to the current investigation and research, it summarizes the relevant problems of AI technology application in drama videos and puts forward some thoughts on the development direction of AI drama videos. It will pave the way for the further study of the application of AI in opera by relevant scholars in the future.